Adjectives as Cultural Mirrors: Exploring Semantic Nuances in Bengkulu Malay - Rustinar, Eli; Kusmiarti, Reni (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study delves into the intricate semantic nuances of adjectives within the Bengkulu Malay Language (bMB), positing that they function beyond simple denotative descriptions to profoundly reflect speakers’ attitudes, emotions, and ingrained cultural identity. Recognizing the critical role of semantics in analyzing the distinctions between literal and connotative meanings, the research employed a rigorous qualitative descriptive methodology. Data were meticulously extracted from written bMB texts, specifically drawing its primary data from the comprehensive book “Pernak-pernik Bahaso Kito Bengkulu”. The analysis is conducted using distributional techniques to analyze the context of the sentences. The investigation successfully identified and classified 166 unique adjectives, categorizing them into three significant dimensions of meaning nuances: 56 adjectives exhibiting emotional nuances, 55 reflecting social nuances, and another 55 imbued with cultural nuances. This detailed classification underscores that bMB adjectives are not merely linguistic labels but critical linguistic tools that embody the community’s local wisdom, communal values, and the deep, symbiotic relationship between language and culture. The findings carry substantial implications, contributing significantly to linguistic and semantic theory by providing empirical evidence for the rich connotative potential of regional languages. This research underscores the crucial role of semantic analysis in understanding and preserving the Bengkulu Malay language, a vital component of Indonesia’s rich linguistic and cultural heritage, and advocates for its continued study and preservation.